(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Solid waste management has become a critical environmental challenge due to its direct implications for public health and resource sustainability. Rapid population growth, urban expansion, and shifts in consumption patterns have led to a steady increase in waste generation, while existing infrastructure often struggles to keep pace with these rising quantities. The complexity of the issue stems from the diverse composition of solid waste—ranging from household and industrial refuse to medical and plastic materials—each of which requires specialized treatment methods to reduce environmental harm. Key obstacles include inefficient collection and sorting systems, reliance on open dumping or uncontrolled burning, and the resulting contamination of air, soil, and groundwater. The problem is further exacerbated by limited public awareness and insufficient recycling policies. Addressing these challenges calls for an integrated approach that prioritizes waste reduction at the source, promotes reuse and recycling, and supports the development of safe and efficient treatment technologies. Improving solid waste management ultimately depends on coordinated efforts among governmental institutions, the private sector, and local communities. Establishing clear regulatory frameworks and supporting sustainable practices can help mitigate the environmental impacts of waste and transform it into a valuable resource that contributes to long-term environmental and economic resilience.